Music and Movement in Hong Kong Kindergartens: Teachers’ Preparation, Perceived Usefulness, Confidence, and Readiness - Alfredo Bautista; Yan-Lam Ho (Revista Electrónica Complutense de Investigación en Educación Musical, 2022)
Few large-scale studies have examined how prepared early childhood educators feel to teach music and movement to young children. This paper is part of a survey study conducted with 1,019 Hong Kong kindergarten teachers. We investigated their prior music and movement educational experiences (extracurricular activities, pre-service courses, in-service professional development), their perceived usefulness of such experiences, as well as their perceived confidence and readiness to teach music and movement in kindergartens. Differences according to teaching experience and educational qualifications were analyzed. Findings reveal the need to strengthen teachers’ preparation in music and movement, especially among beginning educators. Limitations are discussed.